Monitoring of Colorectal Cancer Screening Adherence Among African American Patients of North Florida Community Health Centers - John S. Luque; Gebre-Egziabher Kiros; Askal A. Ali; Sabrina L. Dickey; Matthew Vargas; Deloria R. Jackson; Ryan Mohorne; Tanvee Doddi; Kristin Wallace; Clement K. Gwede (Journal of Cancer Education, 2026)
In the United States, colorectal cancer (CRC) mortality rates are higher in African Americans compared to non-Hispanic whites, partly due to advanced stage cancer diagnosis. Timely CRC screening helps to increase CRC early detection and survival in this population. The objective of this monitoring study was to survey African American patients of Community Health Centers (CHC) in north Florida and to monitor CRC screening adherence (either stool-based or colonoscopy) after they had completed a clinical trial testing a screening education intervention. Seventy-nine African American patients who were between the ages of 45 and 64 years old at the time of initial trial recruitment completed a 24-month follow-up survey, and 44% reported stool-based CRC screening in the last year. Results from the general estimating equations (GEE) model found there was a statistically significant difference in CRC screening adherence by study arm at 24 months where the intervention group was less likely to be up to date than the usual care control (OR = 0.60, 95% CI 0.43–0.83). Married or partnered participants (OR = 1.52, 95% CI 1.31–1.77) and employed participants (OR = 1.34, 95% CI 1.17–1.53) were more likely to be adherent to screening, but female participants were less likely to be adherent (OR = 0.76, 95% CI 0.70–0.82). Participants with higher mistrust in doctors were less likely to have completed screening (OR = 0.93, 95% CI 0.88–0.99). The findings suggest the importance of screening outreach to unmarried, unemployed, female African Americans. The results of this monitoring study indicate one-on-one cancer education with a community health advisor and education on the availability and functionality of electronic patient portals have potential for increasing adherence to recommended CRC screening. The study has implications for measuring CRC screening adherence in community settings.

Sea cucumbers can enhance coral growth and photophysiological performance under field conditions - Cody S. Clements; Mark E. Hay (Coral Reefs, 2026)
Detritivorous sea cucumbers are important processors of reef sediments and have been hypothesized to enhance coral growth by altering local nutrient availability and seawater chemistry, but whether these effects translate into improved coral performance remains untested. We conducted two analogous field experiments in Mo’orea, French Polynesia, to test whether the sea cucumber Holothuria atra enhances coral growth or photosynthetic efficiency. In the first experiment, we enclosed Acropora pulchra with zero versus two sea cucumbers per 0.25 m 2 , approximating natural densities at our site, and found no detectable effect of sea cucumber presence on growth. In 2025, using densities of four per 0.25 m 2 and enclosing three coral species, A. pulchra growth was 41% greater and Pocillopora verrucosa growth was 17% greater in cages with versus without sea cucumbers. The photosynthetic efficiency of Pocillopora verrucosa was also increased, but that of A. pulchra was not. Porites rus showed no significant response for either metric. Thus, sea cucumbers can enhance coral growth and photophysiological performance under field conditions, but these benefits vary across species, response variables, and apparently sea cucumber density. As sea cucumbers have been widely depleted from tropical reefs, identifying the mechanisms and density thresholds governing these effects will be important for understanding the ecological consequences of their loss and their potential role in supporting coral reef stability or recovery.

Fentanyl decreases arterial blood oxygen saturation more than furanylfentanyl in mice due to increased apnea - Catherine Demery; Sierra C. Moore; Kelsey E. Kochan; Mengchu Li; Thomas D. Prince; Benjamin M. Clements; Zhongqi Chen; Jessica R. Whitaker-Fornek; Erica S. Levitt; Jessica P. Anand; John R. Traynor (Psychopharmacology, 2026)
Rationale Fatal opioid overdoses involving synthetic opioids have increased >10-fold over the past 8 years. Fentanyl, a potent synthetic opioid acting at the mu-opioid receptor (MOR), has largely replaced heroin as the predominant illicit opioid available. Various analogs have been synthesized from the fentanyl scaffold, including 2-furanylfentanyl, one of the most trafficked analogs from 2019 to 2024. Despite its prevalence, the in vivo effects of furanylfentanyl are not well characterized, especially regarding respiratory depression. Objectives To characterize furanylfentanyl relative to fentanyl in vitro and compare the effects of both drugs in mouse models of antinociception and respiratory depression. Methods The affinity and potency of fentanyl and furanylfentanyl were determined in CHO cells overexpressing MOR. Male and female CD-1 mice were administered ( i.p. ) fentanyl or furanylfentanyl prior to measuring antinociception (warm-water tail withdrawal), respiration (whole-body plethysmography), or oxygen saturation (pulse oximetry). Results Furanylfentanyl behaves as a partial agonist in vitro relative to fentanyl and morphine but with similar affinity and potency at MOR. In mice, fentanyl and furanylfentanyl produced similar effects on breathing parameters (including rate and inspiration time) that were greater than those induced by morphine, yet only fentanyl caused a drastic, long-lasting depletion of blood oxygen saturation. The discrepancy between effects on breathing and oxygen saturation may be explained by a greater number of apneas induced by fentanyl. Conclusions These results highlight the complexity of fentanyl-induced respiratory depression and indicate that recreational use of 2-furanylfentanyl in humans may pose a greater risk of overdose than morphine but lesser than fentanyl.

Novel application of Distributed Fiber Optic Sensors for real-time monitoring of a composite marine propeller - Maria Xenidou; Kyriaki Tsirka; Andreas Kalogirou; Nick Markov; Valeriy Dimitrov; Clement Retiere; Gabriel Heguy; Thibaut Alleau; Alkiviadis S. Paipetis (Ocean Engineering, 2026)

The fragility of the Uranian moons during the giant planet instability - Matthew S. Clement; Nathan A. Kaib; André Izidoro; Rogerio Deienno (Icarus, 2026)

Phanerozoic continental magmatism: Linking spatiotemporal evolution, isotopic composition, and chemical weathering - Wenrong Cao; Clement Bataille; Xiqiang Zhou; Joel S. Scheingross; Jeremy Tsung-Jui Wu; Hehe Jiang (Earth and Planetary Science Letters, 2026)

Historic coral disturbance versus current coral restoration: insights from Palmyra Atoll - Cody S. Clements; Noam T. Altman-Kurosaki; F. Joseph Pollock; Mark E. Hay (Coral Reefs, 2026)
The utility of passive vs. active coral restoration continues to be debated as reefs decline worldwide. Here, we evaluated the efficacy of coral transplantation into the degraded East and Center lagoons of Palmyra Atoll. Corals have failed to recover in these sites over the eight decades since disturbances associated with World War II, despite high coral cover elsewhere around the atoll that could theoretically provide source propagules. We explicitly compared (i) species beginning to recolonize the lagoons with species common elsewhere at Palmyra, (ii) performance between the East and Center lagoons, and (iii) coral growth at sites near vs. far from causeway inlets as a proxy for the benefits of flow. We found that six common coral species were all physiologically capable of growing in the lagoon, but there were: i) large among-species difference in survival, ii) less, but still significant, differences in growth among species, and iii) localized differences in growth and survival across the eight test locations. Many of these differences appeared to be driven by patterns in fish predation on corals. Survival was greatest for Porites and Pavona species, neither of which have substantially colonized the lagoons. Their superior performance relative to Acropora and Pocillopora species that have begun to recolonize the East Lagoon suggests that transplantation of hardier Porites and Pavona species may accelerate recovery. Coral reef restoration efforts often focus on more threatened and fragile corals like Acropora and Pocillopora . Prioritizing the initial planting of hardier corals like Porites and Pavona may help establish foundational reef functions before introducing more fragile species.

A synthesis of principles for building the social–ecological resilience and adaptive capacity of protected and conserved areas - Graeme S. Cumming; Alta De Vos; Hayley S. Clements; Bekezela Dube; Herve Fritz; Edson Gandiwa; Chloé Guerbois; Nelsiwe P. Mpapane; Dirk. J. Roux (Conservation Biology, 2026)
The long‐term success of protected and conserved areas depends on their capacity to remain relevant to human society while maintaining diverse, functional ecosystems. However, despite long‐standing interest in applying complex systems approaches to foster protected area (PA) social–ecological resilience and adaptive capacity, a gap between theory and practice remains. We reviewed the evolution of overarching principles for resilience management to provide a cohesive synthesis and identify priorities for conservation governance and management. A systematic literature search identified 15 individual articles that together proposed 20 interrelated thematic clusters (themes) of principles. Analysis of connections between themes and publications identified 2 main schools, one with a more institutional focus (the Ostrom school) and the other with a more ecological focus (the Holling school). We assessed the strengths and weaknesses of the combined set of resilience principles with a focus on identifying gaps in current knowledge. Strengths included principles supported by extensive research on ecological diversity, heterogeneity, and collaborative governance. Key gaps relating to PA resilience included 3 interrelated needs for future research and action: developing governance solutions that extend beyond traditional PA boundaries, clarification of the dynamics of the relationship between resilience and transformation agendas, and deeper and more formal inclusion of justice and equity in resilience management. The rigorous establishment, application, and testing of science‐based principles for building and supporting resilience and adaptive capacity, and their translation into conservation actions, remain a critically important goal for conservation science.

Seasonal variation in zooplankton assemblages in Ryder Bay, Adelaide Island, Antarctic Peninsula - Alice Clement; Simon A. Morley; Lloyd S. Peck (Polar Biology, 2026)
Seasonal and inter-annual variations in zooplankton play a vital role in marine ecosystems. In Antarctica, because of the extreme seasonality and ice extent, zooplankton studies are predominantly conducted in summer and are based offshore. Therefore the drivers of variability are poorly understood. Here, we present one of the few year-round studies of seasonality of zooplankton communities at a coastal site in Ryder Bay, Western Antarctic Peninsula (WAP), encompassing both holoplankton and meroplankton. While there were consistent species components to the assemblage, there was also substantial intra- and inter-annual variation throughout the study, suggesting short-term and single-season evaluations are insufficient to provide a comprehensive understanding of zooplanktonic assemblage dynamics and controlling factors. Small copepods and nemertean pilidium (32% and 28% of all individuals seen, respectively) were present throughout all seasons, and both organisms were present in all but one event, peaking at 89% and 90% of individuals sampled, respectively. However, some organisms, such as some species of pteropoda, cnidaria, and echinodermata, were only present once in the 3-year period, suggesting greater overall diversity than this study found and possibly indicating unusual spatial patchiness or multi-year phenologies. Planktonic larvae of benthic species were more abundant in deeper water samples, closer to the seabed, and assemblage composition and abundance were affected by chlorophyll levels. Larvae and zooplankton of pelagic species assemblages were significantly correlated with temperature, salinity, and pigment levels, strongly suggesting links between specific species and environmental conditions, relationships that are likely to be affected by climate change.

Correction to: Thierry B.R. Chopin (1959–2024) – Innovator of Modern IMTA - S. M. C. Robinson; C. Yarish; A. Buschmann; J. Clements; B. A. Costa‑Pierce; A. Hamer; L. Hayashi; C. Hurd; A. Neori; S. Pang; C. Pearce; G. Reid; et al. (Journal of Applied Phycology, 2026)

Microplastics and anammox: Unravelling the hidden threats to nitrogen cycling and microbial resilience - Wajiha Sarfraz; Munawar Hussain; Clement Matthew Chan; Chengrong Chen; Noreen Khalid; Bahar S. Razavi; Mehran Rezaei Rashti (Journal of Hazardous Materials, 2026)

Increased benthic biodiversity and food web recovery after decommissioning of oil and gas infrastructure - Zelin Chen; Tom C. Cameron; Elena Couce; Clement Garcia; Natalie Hicks; Gareth E. Thomas; Murray S. A. Thompson; Corinne Whitby; Eoin J. O'Gorman (Limnology and Oceanography, 2026)
There is a global increase in the decommissioning of offshore oil and gas (O&G) infrastructure at the end of its operating lifetime. However, there is strikingly limited empirical evidence for the environmental and ecological impacts of decommissioning. Here, we employed a meta‐analytical approach on an industry benthic monitoring database to investigate the benthic biodiversity and food web properties of structures sampled in the short term ( 5 yr; scenario 3) after decommissioning. We found reduced species richness and simplified food webs in scenario 1, followed by the first signs of recovery in scenario 2, with a slightly higher proportion of intermediate species and density of food web connections. Food webs recovered further in scenario 3, with a much greater density of interactions, but also more links and longer food chains, while a reduction in generalism and connectance indicated an increased prevalence of specialist species. Our findings demonstrate disturbance risks associated with the decommissioning process in the short term, but a positive recovery trajectory over longer timescales. We highlight the importance of industry collecting more extensive and long‐term data at multiple time points and covering different decommissioning types, establishing a standardized data workflow for integrating with available monitoring efforts, and improving stakeholder participation and data accessibility to support an environmentally sound decommissioning process.

Scene Analysis for Gas Estimation (SAGE): A tool for quantification of diffuse and point-source atmospheric trace gas abundance - Jeffrey L. Hall; Clement S. Chang; Karl Westberg; David M. Tratt (Remote Sensing of Environment, 2025)

Thierry B.R. Chopin (1959–2024) – Innovator of Modern IMTA - S. M. C. Robinson; C. Yarish; A. Buschmann; J. Clements; B. A. Costa-Pierce; A. Hamer; L. Hayashi; C. Hurd; A. Neori; S. Pang; C. Pearce; G. Reid; et al. (Journal of Applied Phycology, 2025)

A scalable, annual aboveground biomass product for monitoring carbon impacts of ecosystem restoration projects - Clement Atzberger; Markus Immitzer; Kyle S. Hemes; Mathias Kästenbauer; Josué López; Talita Terra; Clara Rajadel-Lambistos; Saulo Franco de Souza; Kleber Trabaquini; Nathan Wolff (Remote Sensing of Environment, 2025)

Unlocking opportunities for meaningful participation of land reform beneficiaries in the wildlife economy - Siviwe Shwababa; Matthew F. Child; Alta de Vos; Naledi Mneno; Hayley S. Clements (Land Use Policy, 2025)

Pharmacokinetics and Pharmacodynamics of Nomlabofusp in Non-clinical Studies of Friedreich’s Ataxia - Flavia De Toni; Vanessa Ragaglia; Devin Schecter; Angela S. Miller; Eric Gonzalez; Erik J. Wagner; Xin Xu; R. Mark Payne; Jean-Nicholas Mess; Matthew G. Baile; Adrienne Clements-Egan; Gopi Shankar (The AAPS Journal, 2025)
Nomlabofusp is a cell penetrant peptide-based recombinant fusion protein designed to enter cells and deliver human frataxin into the mitochondria of adults and children with Friedreich’s ataxia. In this article we present non-clinical studies evaluating the pharmacology of nomlabofusp, including in a murine striated muscle tissue frataxin knockout model of Friedreich’s ataxia. We demonstrate that subcutaneous administration of nomlabofusp distributes in a dose-dependent manner to several organs including the dorsal root ganglion, heart, and skeletal muscle, which are known to be predominantly affected in Friedreich’s ataxia, as well as to other tissues, including skin. Plasma nomlabofusp concentrations correlated with levels of human frataxin delivered by nomlabofusp into tissues, and the increases in frataxin were correlated amongst tissues, especially with skin. In the knockout mice, we show that the pharmacokinetics and processing of nomlabofusp were comparable with wild type animals and that treatment with nomlabofusp halts the progression of cardiac dysfunction and significantly increased survival. Together, the findings from these non-clinical studies demonstrate that nomlabofusp exposure increases human frataxin in Friedreich’s ataxia-relevant tissues and provide evidence of pharmacologic effects. Graphical Abstract

Isolation, characterization, HPLC quantification, in-vitro and in-silico evaluations of coumarins and coumarolignans from Blighia unijugata stem with their chemotaxonomic significance - Clement Odunayo Ajiboye; Dorcas Olufunke Moronkola; Arfan Khalid; Akinbo Akinwumi Adesomoju; Sagar S. Bhayye; Yogesh P. Bharitkar; Govind Yadav; Mahendra Kumar Verma (Biochemical Systematics and Ecology, 2025)

Endoparasite communities of New Zealand Penguins differ over time and among species - Jerusha Bennett; Bronwen Presswell; Mikey Little; Clement Lagrue; Trudi Webster; Ludovic Dutoit; Robert Poulin; Ian Davidson; Patrick Cahill; Kate S. Hutson (Marine Biology, 2025)
Parasites can provide valuable insights into the ecology and health of their hosts and the state of the surrounding ecosystem. In this study, we describe the helminth parasite communities infecting penguin species in Otago, New Zealand (little blue penguin, Fiordland crested penguin, Snares crested penguin, erect crested penguin and yellow-eyed penguin). We investigate differences in parasite communities among penguin species, and changes over time for little blue penguins. In total, 19 parasite species representing 8 families (Desmidocercidae, Anisakidae, Acuariidae, Capillariidae, Tetrabothriidae, Heterophyidae, Renicolidae and Polymorphidae) were recorded from 121 penguin individuals. Parasite assemblages differed among penguin species, likely reflective of their differences in diet and feeding strategies. We also observed significant changes in the composition of parasite communities of little blue penguins using samples from a 30-year timespan (1993–2023). There was an overall increase in parasite diversity over time, including some species of potential disease concern, which could reflect a shift in prey availability of fish in the area. Our findings contribute to the understanding of penguin ecology and emphasise the use of parasites as indicators of ecological change.

Correction to: Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2025)

Identifying gaps in the conservation of small wild cats of Southeast Asia - Luca Chiaverini; David W. Macdonald; Andrew J. Hearn; Żaneta Kaszta; Eric Ash; Özgün Emre Can; Phan Channa; Susan M. Cheyne; Gopalasamy Reuben Clements; Iding Achmad Haidir; Jan F. Kamler; Pyae Phyoe Kyaw; et al. (Biodiversity and Conservation, 2025)
Southeast Asia hosts more felid species than any other region and, although smaller (

Antifouling activity exhibited by pyrrolo compound isolated from marine sponge associated bacterium Halobacillus kuroshimensis SNSAB01 against barnacles - S. Nalini; S. Venkatnarayanan; D. Inbakandan; Clarita Clements; S.U. Mohammed Riyaz; T. Stalin Dhas; P. Sriyutha Murthy; G. Dharani (International Biodeterioration & Biodegradation, 2025)

Using Community Composition and Successional Theory to Guide Site‐Specific Coral Reef Management - Orion S. McCarthy; Emily L. A. Kelly; Anela K. Akiona; Samantha M. Clements; Tatiana Martinez; Nicole E. Pedersen; Cole Peralto; Sarah L. Romero; Mitchell H. Smelser; Kristy Wong Stone; Russell T. Sparks; Jennifer E. Smith (Global Change Biology, 2025)
High spatial or temporal variability in community composition makes it challenging for natural resource managers to predict ecosystem trajectories at scales relevant to management. This is commonly the case in nearshore marine environments, where the frequency and intensity of disturbance events vary at the sub‐kilometer to meter scale, creating a patchwork of successional stages within a single ecosystem. The successional stage of a community impacts its stability, recovery potential, and trajectory over time in predictable ways. Here we demonstrate the value of successional theory for interpreting fine‐scale community heterogeneity using Hawaiian coral reefs as a case study. We tracked benthic community dynamics on 36 forereefs over a 6‐year period (2017–2023) that captures impacts from high surf events, a marine heatwave, and unprecedented shifts in human behavior due to the COVID‐19 pandemic. We document high spatial variation in benthic community composition that was only partially explained by island and environmental regime. Through hierarchical clustering, we identify three distinct community types that appear to represent different successional stages of reef development. Reefs belonging to the same community type exhibited similar rates of change in coral cover and structural complexity over time, more so than reefs located on the same island. Importantly, communities that were indicative of early succession (low coral cover reefs dominated by stress‐tolerant corals) were most likely to experience an increase in coral cover over time, while later‐stage successional communities were more likely to experience coral decline. Our findings highlight the influence of life history and successional stage on community trajectories. Accounting for these factors, not simply overall coral cover, is essential for designing effective management interventions. Site‐specific management that accounts for a community's unique composition and history of disturbance is needed to effectively conserve these important ecosystems.

Leopards on the edge: Assessing population status, habitat use, and threats in Southeast Asia - S. Rostro-García; J.F. Kamler; R. Sollmann; G. Balme; R. Sukmasuang; A. Godfrey; S. Saosoong; K. Siripattaranukul; S. Suksavate; W. Thomas; R. Crouthers; V. In; et al. (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Biodiversity of macroalgae does not differentially suppress coral performance: The other side of a biodiversity issue - Cody S. Clements; Zoe A. Pratte; Frank J. Stewart; Mark E. Hay (Ecology, 2024)
Hundreds of studies now document positive relationships between biodiversity and critical ecosystem processes, but as ecological communities worldwide shift toward new species configurations, less is known regarding how the biodiversity of undesirable species will shape the functioning of ecosystems or foundation species. We manipulated macroalgal species richness in experimental field plots to test whether and how the identity and diversity of competing macroalgae affected the growth, survival, and microbiome of a common coral in Mo'orea, French Polynesia. Compared to controls without algal competitors, coral growth was significantly suppressed across three macroalgal monocultures, a polyculture of the same three macroalgae, and plots containing inert seaweed mimics; coral mortality was limited and did not differ significantly among treatments. One macroalga suppressed coral growth significantly less than the other two, but none differed from the inert mimic in terms of coral suppression. The composition, dispersion, and diversity of coral microbiomes in treatments with live macroalgae or inert plastic mimics did not differ from controls experiencing no competition. Microbiome composition differed between two macroalgal monocultures and a monoculture versus plastic mimics, but no other microbiome differences were observed among macroalgal or mimic treatments. Together, these findings suggest that algal diversity does not alter harmful impacts of macroalgae on coral performance, which could be accounted for by physical structure alone in these field experiments. While enhancing biodiversity is a recognized strategy for promoting desirable species, it would be worrisome if biodiversity also enhanced the negative impacts of undesirable species. We documented no such effects in this investigation.

Impacts of climate change on mangrove subsistence fisheries: a global review - Roann P. Alberto; Judith A. Teano; Annie Melinda Paz-Alberto; Mark Anthony B. Tangonan; Hazel Jade E. Villamar; Sarah Clement; David J. S. Montagnes; Andrew P. Morse (Marine Life Science & Technology, 2024)
Climate change will impact coastal ecosystems, threatening subsistence fisheries including those in mangrove forests. Despite their global contributions and roles in nutrition and cultural identity, mangrove subsistence fisheries are poorly studied. Here, we offer a foundation for improving the management of mangrove subsistence fisheries to deal with the impending effects of climate change. This multidisciplinary review—drawing on organismal biology, ecology, fisheries, and social science—focuses on the climate impacts relevant to mangrove ecosystems: heat waves, low-category, and high-category typhoons. First, we provide an overview of the mangroves, their harvestable stocks (fish, crustaceans, molluscs), and the fishers, offering an understanding of how they may be affected by relevant environmental variables; i.e., shifts in temperature, salinity, oxygen, flooding, and sediments. Then, we examine the potential effects of climate change on mangrove stocks and fishers, indicating the scope of impending changes. By combining the above information, we develop a simple model that forecasts the number of “fishing-days” lost by fishers due to climate change over the next decade (between 11 and 21 days will be lost per year per fisher). This indicates which aspects of climate change will have the greatest impacts on stocks and fishers. We found that high-category typhoons had more impacts than heat waves, which in turn had a greater impact than low-category typhoons). Finally, recognising gaps in our knowledge and understanding, we offer recommendations for approaches for future work to improve our predictions.

More realistic planetesimal masses alter Kuiper belt formation models and add stochasticity - Nathan A. Kaib; Alex Parsells; Simon Grimm; Billy Quarles; Matthew S. Clement (Icarus, 2024)

CamTrapAsia : A dataset of tropical forest vertebrate communities from 239 camera trapping studies - Calebe P. Mendes; Wido R. Albert; Zachary Amir; Marc Ancrenaz; Eric Ash; Badrul Azhar; Henry Bernard; Jedediah Brodie; Tom Bruce; Elliot Carr; Gopalasamy Reuben Clements; Glyn Davies; et al. (Ecology, 2024)
Information on tropical Asian vertebrates has traditionally been sparse, particularly when it comes to cryptic species inhabiting the dense forests of the region. Vertebrate populations are declining globally due to land‐use change and hunting, the latter frequently referred as “defaunation.” This is especially true in tropical Asia where there is extensive land‐use change and high human densities. Robust monitoring requires that large volumes of vertebrate population data be made available for use by the scientific and applied communities. Camera traps have emerged as an effective, non‐invasive, widespread, and common approach to surveying vertebrates in their natural habitats. However, camera‐derived datasets remain scattered across a wide array of sources, including published scientific literature, gray literature, and unpublished works, making it challenging for researchers to harness the full potential of cameras for ecology, conservation, and management. In response, we collated and standardized observations from 239 camera trap studies conducted in tropical Asia. There were 278,260 independent records of 371 distinct species, comprising 232 mammals, 132 birds, and seven reptiles. The total trapping effort accumulated in this data paper consisted of 876,606 trap nights, distributed among Indonesia, Singapore, Malaysia, Bhutan, Thailand, Myanmar, Cambodia, Laos, Vietnam, Nepal, and far eastern India. The relatively standardized deployment methods in the region provide a consistent, reliable, and rich count data set relative to other large‐scale pressence‐only data sets, such as the Global Biodiversity Information Facility (GBIF) or citizen science repositories (e.g., iNaturalist), and is thus most similar to eBird. To facilitate the use of these data, we also provide mammalian species trait information and 13 environmental covariates calculated at three spatial scales around the camera survey centroids (within 10‐, 20‐, and 30‐km buffers). We will update the dataset to include broader coverage of temperate Asia and add newer surveys and covariates as they become available. This dataset unlocks immense opportunities for single‐species ecological or conservation studies as well as applied ecology, community ecology, and macroecology investigations. The data are fully available to the public for utilization and research. Please cite this data paper when utilizing the data.

Crash Chronicles: Relative contribution from comets and carbonaceous asteroids to Earth’s volatile budget in the context of an Early Instability - Sarah Joiret; Sean N. Raymond; Guillaume Avice; Matthew S. Clement (Icarus, 2024)

Biosediment assemblages reveal disrupted silica cycling and redox conditions throughout the Rhaetian Stage: Evidence for a precursor event to the end-Triassic mass extinction - Annaka M. Clement; Lydia S. Tackett; Samuel Marolt (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

A race against the clock: Constraining the timing of cometary bombardment relative to Earth’s growth - Sarah Joiret; Sean N. Raymond; Guillaume Avice; Matthew S. Clement; Rogerio Deienno; David Nesvorný (Icarus, 2023)

Association of Preventive Care Attitudes and Beliefs with Colorectal Cancer Screening History among African American Patients of Community Health Centers - John S. Luque; Gebre-Egziabher Kiros; Matthew Vargas; Deloria R. Jackson; Olayemi O. Matthew; Tifini D. Austin; Rima Tawk; Askal A. Ali; Cynthia M. Harris; Kristin Wallace; Clement K. Gwede (Journal of Cancer Education, 2023)

Features of turbulence during wildland fires in forested and grassland environments - Ajinkya Desai; Warren E. Heilman; Nicholas S. Skowronski; Kenneth L. Clark; Michael R. Gallagher; Craig B. Clements; Tirtha Banerjee (Agricultural and Forest Meteorology, 2023)

Sustained secretion of human growth hormone from TheraCyte devices encapsulated with PiggyBac-engineered retinal pigment epithelium cells - Claudia R. Cecchi; Sidsel Alsing; Gustavo P.P. Jesus; Enio A. Zacarias; Lisbeth Kjaer; Michelle S. Clement; Makiko Kumagai-Braesch; Thomas J. Corydon; Paolo Bartolini; Cibele N. Peroni; Lars Aagaard (Tissue and Cell, 2023)

Liver and cardiometabolic markers and conditions in a cross-sectional study of three Australian communities living with environmental per- and polyfluoroalkyl substances contamination - Nina Lazarevic; Kayla S. Smurthwaite; Catherine D'Este; Robyn M. Lucas; Bruce Armstrong; Archie CA. Clements; Susan M. Trevenar; Imogen Gad; Rose Hosking; Hsei Di Law; Jochen Mueller; Jennifer Bräunig; et al. (Environmental Research, 2023)

Psychological distress in three Australian communities living with environmental per- and polyfluoroalkyl substances contamination - Nina Lazarevic; Kayla S. Smurthwaite; Philip J. Batterham; Jo Lane; Susan M. Trevenar; Catherine D'Este; Archie C.A. Clements; Amelia L. Joshy; Rose Hosking; Imogen Gad; Aparna Lal; Hsei Di Law; et al. (Science of The Total Environment, 2023)

Nanomaterials as catalysts for CO2 transformation into value-added products: A review - Yakubu Adekunle Alli; Peter Olusakin Oladoye; Onome Ejeromedoghene; Owolabi Mutolib Bankole; Oyekunle Azeez Alimi; Elizabeth Oyinkansola Omotola; Clement Ajibade Olanrewaju; Karine Philippot; Adeyemi S. Adeleye; Adeniyi Sunday Ogunlaja (Science of The Total Environment, 2023)

Mercury’s formation within the early instability scenario - Matthew S. Clement; John E. Chambers; Nathan A. Kaib; Sean N. Raymond; Alan P. Jackson (Icarus, 2023)

Comparisons of the core and mantle compositions of earth analogs from different terrestrial planet formation scenarios - Jesse T. Gu; Rebecca A. Fischer; Matthew C. Brennan; Matthew S. Clement; Seth A. Jacobson; Nathan A. Kaib; David P. O'Brien; Sean N. Raymond (Icarus, 2023)

Centenarian clocks: epigenetic clocks for validating claims of exceptional longevity - Eric Dec; James Clement; Kaiyang Cheng; George M. Church; Michael B. Fossel; David H. Rehkopf; Luis Rosero-Bixby; Michael S. Kobor; David TS. Lin; Ake T. Lu; Zhe Fei; Wei Guo; et al. (GeroScience, 2023)
Claims surrounding exceptional longevity are sometimes disputed or dismissed for lack of credible evidence. Here, we present three DNA methylation-based age estimators (epigenetic clocks) for verifying age claims of centenarians. The three centenarian clocks were developed based on n = 7039 blood and saliva samples from individuals older than 40, including n = 184 samples from centenarians, 122 samples from semi-supercentenarians (aged 105 +), and 25 samples from supercentenarians (aged 110 +). The oldest individual was 115 years old. Our most accurate centenarian clock resulted from applying a neural network model to a training set composed of individuals older than 40. An epigenome-wide association study of age in different age groups revealed that age effects in young individuals (age < 40) are correlated ( r = 0.55) with age effects in old individuals (age > 90). We present a chromatin state analysis of age effects in centenarians. The centenarian clocks are expected to be useful for validating claims surrounding exceptional old age.

Taphonomic and diagenetic implications of reduction spot formation in Cretaceous red beds from the Jiaolai Basin, Eastern China - Wenzhao Fu; Peter Turner; Thomas Clements; Alan R.T. Spencer; Jifeng Yu; Yu Yang; Bangjie Guo; Zhenguo Ning; Xizhun Zhuo; Michael S. Riley; Jason Hilton (Journal of Asian Earth Sciences, 2023)

Ecosystem-based adaptation in Africa: integrating mitigation and adaptation - Jonty Rawlins; Struan Monteith; Felix Kanungwe Kalaba; Hayley S. Clements (Regional Environmental Change, 2023)

Sedimentological and facies characterization in the modelling of the Turonian sandstone reservoir package, Jubilee field, Ghana - Ebenezer Ansah; Anthony Ewusi; Eric Thompson Brantson; Jerry S. Y. Kuma; Saka A. Opeloye; Boadi K. Obeng; Clement Nuamah (Modeling Earth Systems and Environment, 2023)

Planktonic functional diversity changes in synchrony with lake ecosystem state - Duncan A. O'Brien; Gideon Gal; Stephen J. Thackeray; Shin‐ichiro S. Matsuzaki; Christopher F. Clements (Global Change Biology, 2023)
Managing ecosystems to effectively preserve function and services requires reliable tools that can infer changes in the stability and dynamics of a system. Conceptually, functional diversity (FD) appears as a sensitive and viable monitoring metric stemming from suggestions that FD is a universally important measure of biodiversity and has a mechanistic influence on ecological processes. It is however unclear whether changes in FD consistently occur prior to state responses or vice versa, with no current work on the temporal relationship between FD and state to support a transition towards trait‐based indicators. There is consequently a knowledge gap regarding when functioning changes relative to biodiversity change and where FD change falls in that sequence. We therefore examine the lagged relationship between planktonic FD and abundance‐based metrics of system state (e.g. biomass) across five highly monitored lake communities using both correlation and cutting edge non‐linear empirical dynamic modelling approaches. Overall, phytoplankton and zooplankton FD display synchrony with lake state but each lake is idiosyncratic in the strength of relationship. It is therefore unlikely that changes in plankton FD are identifiable before changes in more easily collected abundance metrics. These results highlight the power of empirical dynamic modelling in disentangling time lagged relationships in complex multivariate ecosystems, but suggest that FD cannot be generically viable as an early indicator. Individual lakes therefore require consideration of their specific context and any interpretation of FD across systems requires caution. However, FD still retains value as an alternative state measure or a trait representation of biodiversity when considered at the system level.

Prediction of inotropic effect based on calcium transients in human iPSC-derived cardiomyocytes and machine learning - Hongbin Yang; Olga Obrezanova; Amy Pointon; Will Stebbeds; Jo Francis; Kylie A. Beattie; Peter Clements; James S. Harvey; Graham F. Smith; Andreas Bender (Toxicology and Applied Pharmacology, 2023)

Rethinking the role of the giant planet instability in terrestrial planet formation models - Matthew S. Clement; Rogerio Deienno; André Izidoro (Icarus, 2023)

Platelets from 13-lined ground squirrels are resistant to cold storage lesions - N. Splinter; A. Mancosky; C. Laffin; M. Clement; M. Nisius; B. Arbs; E. BonoAnno; E. Bartig; S. Cooper (Journal of Comparative Physiology B, 2023)

A Global-Scale Assessment of Water Resources and Vegetation Cover Dynamics in Relation with the Earth Climate Gradient - Clement D. D. Sohoulande; Herve Awoye; Kossi S. Nouwakpo; Selim Dogan; Ariel A. Szogi; Ken C. Stone; Jerry H. Martin (Remote Sensing in Earth Systems Sciences, 2022)

Variance of coral anti-pathogen defense in response to transplantation between coral- and macroalgal-dominated reefs - Deanna S. Beatty; Cody S. Clements; Jinu Mathew Valayil; Simone Y. Jarvis; Kim B. Ritchie; Frank J. Stewart; Mark E. Hay (Coral Reefs, 2022)

A perspective on molecular signalling dysfunction, its clinical relevance and therapeutics in autism spectrum disorder - Sushmitha S. Purushotham; Neeharika M. N. Reddy; Michelle Ninochka D’Souza; Nilpawan Roy Choudhury; Anusa Ganguly; Niharika Gopalakrishna; Ravi Muddashetty; James P. Clement (Experimental Brain Research, 2022)

Unravelling the Structural Mechanism of Action of 5-methyl-5-[4-(4-oxo-3H-quinazolin-2-yl)phenyl]imidazolidine-2,4-dione in Dual-Targeting Tankyrase 1 and 2: A Novel Avenue in Cancer Therapy - Xylia Q. Peters; Clement Agoni; Mahmoud E. S. Soliman (Cell Biochemistry and Biophysics, 2022)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Lessons From the Western Atlantic Lionfish Invasion to Inform Management in the Mediterranean - Aylin Ulman; Fadilah Z. Ali; Holden E. Harris; Mohammad Adel; Sara A. A. Al Mabruk; Michel Bariche; Allison C. Candelmo; Jennifer K. Chapman; Burak Ali Çiçek; Kaylin R. Clements; Alexander Q. Fogg; Stacy Frank; et al. (Frontiers in Marine Science, 2022)
Major invasions of Indo-Pacific lionfish ( Pterois volitans and P. miles ) are underway in the Western Atlantic Ocean and the Mediterranean Sea. While the establishment of lionfish in the Western Atlantic is perhaps the most well-studied marine fish invasion to date, the rapidly expanding invasion in the Mediterranean is more recent and has received less attention. Here we review and synthesize successes and failures from two decades of lionfish management in the Western Atlantic to give policy recommendations for their management in the Mediterranean. Two failed approaches that were attempted multiple times in the Western Atlantic and that we advise against are (1) feeding lionfish to native fish to promote predation and (2) implementing bounty programs to incentivize lionfish harvest. Broadly, the most important management lessons that we recommend include (1) conducting routine removals by spearfishing with scuba, which can effectively suppress local abundances of lionfish; (2) encouraging the development of recreational and commercial lionfish fisheries, which can promote long-term, sustainable lionfish population control; and, (3) engaging local communities and resource users (e.g., with lionfish removal tournaments), which can concurrently achieve multiple objectives of promoting lionfish removals, market-development, research, and public education. Managers in the Western Atlantic often needed to adapt current conservation policies to enable lionfish removals in areas where spearfishing with scuba was otherwise prohibited for conservation purposes. The risk of abusing these policies was mitigated through the use of gear restrictions, diver trainings, and through participatory approaches that integrated scuba divers and stakeholder organizations in lionfish research and management. Our review of policies and practices in the Mediterranean Sea found that many of our recommended lionfish management approaches are not being done and indicate potential opportunities to implement these. We expect and fully recommend that work continues towards multinational cooperation to facilitate regional coordination of research, control, and management efforts with respect to the Mediterranean lionfish invasion. As with other major biological invasions, lionfish are unconstrained by political borders and their control will require rapid and strategic management approaches with broad cooperation among and between governments and stakeholders.

EMA- Versus PMA-Amplicon-Based Sequencing to Elucidate the Viable Bacterial Community in Rainwater - B. Reyneke; M. Waso; T. Ndlovu; T. Clements; B. Havenga; S. Khan; W. Khan (Water, Air, & Soil Pollution, 2022)

Sub-lethal effects of organophosphates and synthetic pyrethroid insecticides on muscle tissue transaminases of Oreochromis niloticus in vivo - Muhammad Amin; Masarrat Yousuf; Naveed Ahmad; Mohammad Attaullah; Muhammad Ikram; Attia A. Abou Zaid; Clement Ameh Yaro; Eida M. Alshammari; Yaser S. Binnaser; Gaber El-Saber Batiha; Islam Dad Buneri (Toxicological Research, 2022)

Engaging the Community on Colorectal Cancer Screening Education: Focus Group Discussions Among African Americans - John S. Luque; Matthew Vargas; Kristin Wallace; Olayemi O. Matthew; Rima Tawk; Askal A. Ali; Gebre-Egziabher Kiros; Cynthia M. Harris; Clement K. Gwede (Journal of Cancer Education, 2022)

Did the historic overharvesting of sea cucumbers make coral more susceptible to pathogens? - Natalie Grayson; Cody S. Clements; Alexandra A. Towner; Deanna S. Beatty; Mark E. Hay (Coral Reefs, 2022)

Prioritizing the Catalytic Gatekeepers through Pan- Inhibitory Mechanism of Entrectinib against ALK, ROS1 and TRKA Tyrosine Kinases - Elliasu Y. Salifu; Abdul Rashid Issahaku; Clement Agoni; Mahmoud A. A. Ibrahim; Nlooto Manimbulu; Mahmoud E. S. Soliman (Cell Biochemistry and Biophysics, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A “Dirty” Footprint: Macroinvertebrate diversity in Amazonian Anthropic Soils - Wilian C. Demetrio; Ana C. Conrado; Agno N. S. Acioli; Alexandre C. Ferreira; Marie L. C. Bartz; Samuel W. James; Elodie da Silva; Lilianne S. Maia; Gilvan C. Martins; Rodrigo S. Macedo; David W. G. Stanton; Patrick Lavelle; et al. (Global Change Biology, 2021)
Amazonian rainforests, once thought to be pristine wilderness, are increasingly known to have been widely inhabited, modified, and managed prior to European arrival, by human populations with diverse cultural backgrounds. Amazonian Dark Earths (ADEs) are fertile soils found throughout the Amazon Basin, created by pre‐Columbian societies with sedentary habits. Much is known about the chemistry of these soils, yet their zoology has been neglected. Hence, we characterized soil fertility, macroinvertebrate communities, and their activity at nine archeological sites in three Amazonian regions in ADEs and adjacent reference soils under native forest (young and old) and agricultural systems. We found 673 morphospecies and, despite similar richness in ADEs (385 spp.) and reference soils (399 spp.), we identified a tenacious pre‐Columbian footprint, with 49% of morphospecies found exclusively in ADEs. Termite and total macroinvertebrate abundance were higher in reference soils, while soil fertility and macroinvertebrate activity were higher in the ADEs, and associated with larger earthworm quantities and biomass. We show that ADE habitats have a unique pool of species, but that modern land use of ADEs decreases their populations, diversity, and contributions to soil functioning. These findings support the idea that humans created and sustained high‐fertility ecosystems that persist today, altering biodiversity patterns in Amazonia.

Molecular characterization of clinical carbapenem-resistant Enterobacterales from Qatar - Fatma Ben Abid; Clement K. M. Tsui; Yohei Doi; Anand Deshmukh; Christi L. McElheny; William C. Bachman; Erin L. Fowler; Ahmed Albishawi; Kamran Mushtaq; Emad B. Ibrahim; Sanjay H. Doiphode; Manal M. Hamed; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
One hundred forty-nine carbapenem-resistant Enterobacterales from clinical samples obtained between April 2014 and November 2017 were subjected to whole genome sequencing and multi-locus sequence typing. Klebsiella pneumoniae (81, 54.4%) and Escherichia coli (38, 25.5%) were the most common species. Genes encoding metallo-β-lactamases were detected in 68 (45.8%) isolates, and OXA-48-like enzymes in 60 (40.3%). bla NDM-1 (45; 30.2%) and bla OXA-48 (29; 19.5%) were the most frequent. KPC-encoding genes were identified in 5 (3.6%) isolates. Most common sequence types were E. coli ST410 (8; 21.1%) and ST38 (7; 18.4%), and K. pneumoniae ST147 (13; 16%) and ST231 (7; 8.6%).

An agenda for research and action toward diverse and just futures for life on Earth - C. Wyborn; J. Montana; N. Kalas; S. Clement; F. Davila; N. Knowles; E. Louder; M. Balan; J. Chambers; L. Christel; T. Forsyth; G. Henderson; et al. (Conservation Biology, 2021)
Decades of research and policy interventions on biodiversity have insufficiently addressed the dual issues of biodiversity degradation and social justice. New approaches are therefore needed. We devised a research and action agenda that calls for a collective task of revisiting biodiversity toward the goal of sustaining diverse and just futures for life on Earth. Revisiting biodiversity involves critically reflecting on past and present research, policy, and practice concerning biodiversity to inspire creative thinking about the future. The agenda was developed through a 2‐year dialogue process that involved close to 300 experts from diverse disciplines and locations. This process was informed by social science insights that show biodiversity research and action is underpinned by choices about how problems are conceptualized. Recognizing knowledge, action, and ethics as inseparable, we synthesized a set of principles that help navigate the task of revisiting biodiversity. The agenda articulates 4 thematic areas for future research. First, researchers need to revisit biodiversity narratives by challenging conceptualizations that exclude diversity and entrench the separation of humans, cultures, economies, and societies from nature. Second, researchers should focus on the relationships between the Anthropocene, biodiversity, and culture by considering humanity and biodiversity as tied together in specific contexts. Third, researchers should focus on nature and economies by better accounting for the interacting structures of economic and financial systems as core drivers of biodiversity loss. Finally, researchers should enable transformative biodiversity research and action by reconfiguring relationships between human and nonhuman communities in and through science, policy, and practice. Revisiting biodiversity necessitates a renewed focus on dialogue among biodiversity communities and beyond that critically reflects on the past to channel research and action toward fostering just and diverse futures for human and nonhuman life on Earth.

The killer within: Endogenous bacteria accelerate oyster mortality during sustained anoxia - Michael R. S. Coffin; Jeff C. Clements; Luc A. Comeau; Thomas Guyondet; Michelle Maillet; Laura Steeves; Keryn Winterburn; José M. F. Babarro; Martin A. Mallet; Rémy Haché; Luke A. Poirier; Saswati Deb; et al. (Limnology and Oceanography, 2021)
Sustained periods of anoxia, driven by eutrophication, threaten coastal marine systems and can lead to mass mortalities of even resilient animals such as bivalves. While mortality rates under anoxia are well‐studied, the specific mechanism(s) of mortality are less clear. We used a suite of complementary techniques (LT50, histology, 16S rRNA amplicon sequencing, and valvometry) to show that the proliferation of anaerobic bacteria within eastern oysters ( Crassostrea virginica ) accelerates mortality rate under anoxic conditions. Manipulative laboratory experiments revealed that oyster survival under anoxic conditions was halved when bacteria were present compared to when they were excluded by the broad‐spectrum antibiotic chloramphenicol. Histological assessments supported this mechanism and showed infiltration of bacteria in oysters that were not treated with antibiotics compared to a general lack of bacteria when oysters were treated with antibiotics. 16S rRNA amplicon sequencing failed to identify any particular genera of bacteria responsible for mortality, rather a diversity of endogenous anaerobic and/or sulfate‐reducing bacteria were common among oysters. In addition, monitoring of oyster valve gaping behavior in the field revealed that oysters showed remarkable valve closure synchrony when first exposed to anoxia. However, oysters periodically opened throughout anoxia/hypoxia in both the lab and field, suggesting that the infiltration of exogenous bacteria from the environment may also influence mortality rates under natural settings. Coupled with previous studies, we posit that mass mortality events in a wide range of coastal bivalves are likely the result of co‐morbidity from asphyxiation and bacterial processes.

Climate change in the context of whole-farming systems: opportunities for improved outreach - R. S. Clements; S. K. Birthisel; A. Daigneault; E. Gallandt; D. Johnson; T. Wentworth; M. T. Niles (Climatic Change, 2021)
Climate change poses a challenge to farming systems worldwide. However, existing research suggests that farmers and those providing outreach may have different climate change perspectives, and there is little understanding of how farmers prioritize climate change compared with other aspects of their farming system. To compare how farmers and outreach professionals in northern New England consider climate change within the context of whole-farming systems, we conducted mental modeling interviews with 33 farmers and 16 outreach professionals. Despite being primed to consider climate during the interviews, only 24% of farmers and 25% of outreach professionals included climate in their mental models. Key differences arose in both group’s perceptions of weather: outreach professionals focused on connections between good weather and biophysical factors, while farmers drew additional connections to factors like quality of life and overall farm success . Social factors including community well-being , public education , and farm success were significantly more likely to be included ( P < 0.05), and in some cases were more influential, in farmer models compared to outreach professional models. We conclude that farmer participants did not perceive climate to be a central factor of their farming systems, and valued human and social dimensions more highly than outreach professionals perceived. These factors may warrant special consideration in efforts to make outreach meaningful to local contexts, along with framing climate change within its broader relationship to other farming system aspects. Interdisciplinary teams may be helpful in developing outreach approaches that fully contextualize climate change within farmers’ complex whole-farm management perspectives.

C60 in olive oil causes light-dependent toxicity and does not extend lifespan in mice - Kristopher J. Grohn; Brandon S. Moyer; Danique C. Wortel; Cheyanne M. Fisher; Ellie Lumen; Anthony H. Bianchi; Kathleen Kelly; Paul S. Campbell; Douglas E. Hagrman; Roger G. Bagg; James Clement; Aaron J. Wolfe; et al. (GeroScience, 2021)

Genetic structure and diversity identify incipient domestication of Piquiá [Caryocar villosum (Aubl.) pers.] along the lower Tapajós River, Brazilian Amazonia - Ana Flávia Francisconi; Rubana Palhares Alves; Charles R. Clement; Gabriel Dequigiovanni; Igor A. S. de Carvalho; Elizabeth A. Veasey (Genetic Resources and Crop Evolution, 2021)

Molecular Basis of P131 Cryptosporidial-IMPDH Selectivity—A Structural, Dynamical and Mechanistic Stance - Kehinde F. Omolabi; Clement Agoni; Fisayo A. Olotu; Mahmoud E. S. Soliman (Cell Biochemistry and Biophysics, 2021)

Convergence, continuity, and community: a framework for enabling emerging leaders to build climate solutions in agriculture, forestry, and aquaculture - S. K. Birthisel; B. A. Eastman; A. R. Soucy; M. Paul; R. S. Clements; A. White; M. P. Acquafredda; W. Errickson; L-H. Zhu; M. C. Allen; S. A. Mills; G. Dimmig; et al. (Climatic Change, 2020)

‘Polymorphism-aided’ Selective Targeting and Inhibition of Caspase-6 by a Novel Allosteric Inhibitor Towards Efficient Alzheimer’s Disease Treatment - Ransford Oduro Kumi; Clement Agoni; Abdul Rashid Issahaku; Fisayo A. Olotu; Mahmoud E. S. Soliman (Cell Biochemistry and Biophysics, 2020)

An Update on the Pharmacological Usage of Curcumin: Has it Failed in the Drug Discovery Pipeline? - Fisayo Olotu; Clement Agoni; Opeyemi Soremekun; Mahmoud E. S. Soliman (Cell Biochemistry and Biophysics, 2020)

Does temperature constrain diet choice in a marine herbivorous fish? - Jethro S. Johnson; David Raubenheimer; Sarah J. Bury; Kendall D. Clements (Marine Biology, 2020)

Use of standardized methods to improve extinction‐risk classification - Caitlin C. Mothes; Stephanie L. Clements; Dishane K. Hewavithana; Hunter J. Howell; Aaron S. David; Nicole D. Leventhal; Christopher A. Searcy (Conservation Biology, 2020)
Standardized classification methods based on quantifiable risk metrics are critical for evaluating extinction threats because they increase objectivity, consistency, and transparency of listing decisions. Yet, in the United States, neither federal nor state agencies use standardized methods for listing species for legal protection, which could put listing decisions at odds with the magnitude of the risk. We used a recently developed set of quantitative risk metrics for California herpetofauna as a case study to highlight discrepancies in listing decisions made without standardized methods. We also combined such quantitative metrics with classification tree analysis to attempt to increase the transparency of previous listing decisions by identifying the criteria that had inherently been given the most weight. Federally listed herpetofauna in California scored significantly higher on the risk‐metric spectrum than those not federally listed, whereas state‐listed species did not score any higher than species that were not state listed. Based on classification trees, state endemism was the most important predictor of listing status at the state level and distribution trend (decline in a species’ range size) and population trend (decline in a species’ abundance at localized sites) were the most important predictors at the federal level. Our results emphasize the need for governing bodies to adopt standardized methods for assessing conservation risk that are based on quantitative criteria. Such methods allow decision makers to identify criteria inherently given the most weight in determining listing status, thus increasing the transparency of previous listing decisions, and produce an unbiased comparison of conservation threat across all species to promote consistency, efficiency, and effectiveness of the listing process.

Paternally‐biased gene expression follows kin‐selected predictions in female honey bee embryos - Nicholas M. A. Smith; Boris Yagound; Emily J. Remnant; Charles S. P. Foster; Gabriele Buchmann; Michael H. Allsopp; Clement F. Kent; Amro Zayed; Stephen A. Rose; Kitty Lo; Alyson Ashe; Brock A. Harpur; et al. (Molecular Ecology, 2020)
The Kinship Theory of Genomic Imprinting (KTGI) posits that, in species where females mate with multiple males, there is selection for a male to enhance the reproductive success of his offspring at the expense of other males and his mating partner. Reciprocal crosses between honey bee subspecies show parent‐of‐origin effects for reproductive traits, suggesting that males modify the expression of genes related to female function in their female offspring. This effect is likely to be greater in the Cape honey bee ( Apis mellifera capensis ), because a male's daughters have the unique ability to produce female offspring that can develop into reproductive workers or the next queen without mating. We generated reciprocal crosses between Capensis and another subspecies and used RNA‐seq to identify transcripts that are over‐ or underexpressed in the embryos, depending on the parental origin of the gene. As predicted, 21 genes showed expression bias towards the Capensis father's allele in colonies with a Capensis father, with no such bias in the reciprocal cross. A further six genes showed a consistent bias towards expression of the father's allele across all eight colonies examined, regardless of the direction of the cross. Consistent with predictions of the KTGI, six of the 21 genes are associated with female reproduction. No gene consistently showed overexpression of the maternal allele .

Human Rhinovirus Inhibition Through Capsid “Canyon” Perturbation: Structural Insights into The Role of a Novel Benzothiophene Derivative - Clement Agoni; Pritika Ramharack; Geraldene Munsamy; Mahmoud E. S. Soliman (Cell Biochemistry and Biophysics, 2020)

Genomic Diversity of Three Brazilian Native Food Crops Based on Double-Digest Restriction Site-Associated DNA Sequencing - Alessandro Alves-Pereira; Mariana Novello; Gabriel Dequigiovanni; José Baldin Pinheiro; Pedro H. S. Brancalion; Elizabeth Ann Veasey; Charles R. Clement; Anete Pereira de Souza; Maria Imaculada Zucchi (Tropical Plant Biology, 2019)

Presence and distribution of progerin in HGPS cells is ameliorated by drugs that impact on the mevalonate and mTOR pathways - Craig S. Clements; Mehmet U. Bikkul; Wendy Ofosu; Christopher Eskiw; David Tree; Evgeny Makarov; Ian R. Kill; Joanna M. Bridger (Biogerontology, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Farnesyltransferase inhibitor and rapamycin correct aberrant genome organisation and decrease DNA damage respectively, in Hutchinson–Gilford progeria syndrome fibroblasts - Mehmet U. Bikkul; Craig S. Clements; Lauren S. Godwin; Martin W. Goldberg; Ian R. Kill; Joanna M. Bridger (Biogerontology, 2018)

Carbon emissions from South‐East Asian peatlands will increase despite emission‐reduction schemes - Lahiru S. Wijedasa; Sean Sloan; Susan E. Page; Gopalasamy R. Clements; Massimo Lupascu; Theodore A. Evans (Global Change Biology, 2018)
Carbon emissions from drained peatlands converted to agriculture in South‐East Asia (i.e., Peninsular Malaysia, Sumatra and Borneo) are globally significant and increasing. Here, we map the growth of South‐East Asian peatland agriculture and estimate CO 2 emissions due to peat drainage in relation to official land‐use plans with a focus on the reducing emissions from deforestation and degradation ( REDD +)‐related Indonesian moratorium on granting new concession licences for industrial agriculture and logging. We find that, prior to 2010, 35% of South‐East Asian peatlands had been converted to agriculture, principally by smallholder farmers (15% of original peat extent) and industrial oil palm plantations (14%). These conversions resulted in 1.46–6.43 Gt CO 2 of emissions between 1990 and 2010. This legacy of historical clearances on deep‐peat areas will contribute 51% (4.43–11.45 Gt CO 2 ) of projected future peatland CO 2 emissions over the period 2010–2130. In Indonesia, which hosts most of the region's peatland and where concession maps are publicly available, 70% of peatland conversion to agriculture occurred outside of known concessions for industrial plantation development, with smallholders accounting for 60% and industrial oil palm accounting for 34%. Of the remaining Indonesian peat swamp forest ( PSF ), 45% is not protected, and its conversion would amount to CO 2 emissions equivalent to 0.7%–2.3% (5.14–14.93 Gt) of global fossil fuel and cement emissions released between 1990 and 2010. Of the peatland extent included in the moratorium, 48% was no longer forested, and of the PSF included, 40%–48% is likely to be affected by drainage impacts from agricultural areas and will emit CO 2 over time. We suggest that recent legislation and policy in Indonesia could provide a means of meaningful emission reductions if focused on revised land‐use planning, PSF conservation both inside and outside agricultural concessions, and the development of agricultural practices based on rehabilitating peatland hydrological function.

Eating in an acidifying ocean: a quantitative review of elevated CO2 effects on the feeding rates of calcifying marine invertebrates - Jeff C. Clements; Elizabeth S. Darrow (Hydrobiologia, 2018)

Staurosporine-induced apoptotic water loss is cell- and attachment-specific - Michael A. Model; Nathan J. Mudrak; Priyanka S. Rana; Robert J. Clements (Apoptosis, 2018)

Neurodegenerative diseases: model organisms, pathology and autophagy - S. N. Suresh; Vijaya Verma; Shruthi Sateesh; James P. Clement; Ravi Manjithaya (Journal of Genetics, 2018)

Citrus Epicarp-Derived Biochar Reduced Cd Uptake and Ameliorates Oxidative Stress in Young Abelmoschus esculentus (L.) Moench (okra) Under Low Cd Stress - Clement O. Ogunkunle; Mayank Varun; Iyanuoluwa G. Ogundele; Kehinde S. Olorunmaiye; Manoj S. Paul (Bulletin of Environmental Contamination and Toxicology, 2018)

Traps and transformations influencing the financial viability of tourism on private‐land conservation areas - Hayley S. Clements; Graeme S. Cumming (Conservation Biology, 2018)
The ability of private conservation organizations to remain financially viable is a key factor influencing their effectiveness. One‐third of financially motivated private‐land conservation areas (PLCAs) surveyed in South Africa are unprofitable, raising questions about landowners’ abilities to effectively adapt their business models to the socioeconomic environment. In any complex system, options for later adaptation can be constrained by starting conditions (path dependence). We tested 3 hypothesized drivers of path dependence in PLCA ecotourism and hunting business models: (H1) the initial size of a PLCA limits the number of mammalian game and thereby predators that can be sustained; (H2) initial investments in infrastructure limit the ability to introduce predators; and (H3) rainfall limits game and predator abundance. We further assessed how managing for financial stability (optimized game stocking) or ecological sustainability (allowing game to fluctuate with environmental conditions) influenced the ability to overcome path dependence. A mechanistic PLCA model based on simple ecological and financial rules was run for different initial conditions and management strategies, simulating landowner options for adapting their business model annually. Despite attempts by simulated landowners to increase profits, adopted business models after 13 years were differentiated by initial land and infrastructural assets, supporting H1 and H2. A conservation organization's initial assets can cause it to become locked into a financially vulnerable business model. In our 50‐year simulation, path dependence was overcome by fewer of the landowners who facilitated natural ecological variability than those who maintained constant hunting rates and predator numbers, but the latter experienced unsustainably high game densities in low rainfall years. Management for natural variability supported long‐term ecological sustainability but not shorter term socioeconomic sustainability for PLCAs. Our findings highlight trade‐offs between ecological and economic sustainability and suggest a role for governmental support of the private conservation industry.

The nutritional basis of seasonal selective feeding by a marine herbivorous fish - Jethro S. Johnson; Kendall D. Clements; David Raubenheimer (Marine Biology, 2017)

Positives and pathologies of natural resource management on private land‐conservation areas - Hayley S. Clements; Graeme S. Cumming (Conservation Biology, 2017)
In managed natural resource systems, such as fisheries and rangelands, there is a recognized trade‐off between managing for short‐term benefits and managing for longer term resilience. Management actions that stabilize ecological attributes or processes can improve productivity in the supply of ecosystem goods and services in the short term but erode system resilience at longer time scales. For example, fire suppression in rangelands can increase grass biomass initially but ultimately result in an undesirable, shrub‐dominated system. Analyses of this phenomenon have focused largely on how management actions influence slow‐changing biophysical system attributes (such as vegetation composition). Data on the frequency of management actions that reduce natural ecological variation on 66 private land‐conservation areas (PLCAs) in South Africa were used to investigate how management actions are influenced by manager decision‐making approaches, a largely ignored part of the problem. The pathology of natural resource management was evident on some PLCAs: increased focus on revenue‐generation in decision making resulted in an increased frequency of actions to stabilize short‐term variation in large mammal populations, which led to increased revenues from ecotourism or hunting. On many PLCAs, these management actions corresponded with a reduced focus on ecological monitoring and an increase in overstocking of game (i.e., ungulate species) and stocking of extralimitals (i.e., game species outside their historical range). Positives in natural resource management also existed. Some managers monitored slower changing ecological attributes, which resulted in less‐intensive management, fewer extralimital species, and lower stocking rates. Our unique, empirical investigation of monitoring‐management relationships illustrates that management decisions informed by revenue monitoring versus ecological monitoring can have opposing consequences for natural resource productivity and sustainability. Promoting management actions that maintain resilience in natural resource systems therefore requires cognizance of why managers act the way they do and how these actions can gradually shift managers toward unsustainable strategies.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

The neuronal metabolite NAA regulates histone H3 methylation in oligodendrocytes and myelin lipid composition - N. K. Singhal; H. Huang; S. Li; R. Clements; J. Gadd; A. Daniels; E. E. Kooijman; P. Bannerman; T. Burns; F. Guo; D. Pleasure; E. Freeman; et al. (Experimental Brain Research, 2017)

Erratum to: Development and validation of the biobanking attitudes and knowledge survey-Spanish (BANKS-SP) - Mariana Arevalo; Paul B. Jacobsen; Clement K. Gwede; Cathy D. Meade; Gwendolyn P. Quinn; John S. Luque; Gloria I. San Miguel; Dale Watson; Kristen J. Wells (Journal of Community Genetics, 2016)

Development and validation of the biobanking attitudes and knowledge survey-Spanish (BANKS-SP) - Mariana Arevalo; Paul B. Jacobsen; Clement K. Gwede; Cathy D. Meade; Gwendolyn P. Quinn; John S. Luque; Gloria San Miguel; Dale Watson; Kristen J. Wells (Journal of Community Genetics, 2016)

Quantitative detection of viable helminth ova from raw wastewater, human feces, and environmental soil samples using novel PMA-qPCR methods - P. Gyawali; W. Ahmed; J. P. S. Sidhu; S. V. Nery; A. C. Clements; R. Traub; J. S. McCarthy; S. Llewellyn; P. Jagals; S. Toze (Environmental Science and Pollution Research, 2016)

Scarless wound healing: finding the right cells and signals - Tripp Leavitt; Michael S. Hu; Clement D. Marshall; Leandra A. Barnes; H. Peter Lorenz; Michael T. Longaker (Cell and Tissue Research, 2016)

Feasibility Study of Engaging Barbershops for Prostate Cancer Education in Rural African-American Communities - John S. Luque; Siddhartha Roy; Yelena N. Tarasenko; Levi Ross; Jarrett Johnson; Clement K. Gwede (Journal of Cancer Education, 2015)

Discordance between nuclear and mitochondrial DNA analyses of population structure in closely related triplefin fishes (Forsterygion lapillum and F. capito, F. Tripterygiidae) supports speciation with gene flow - M. Rabone; S. D. Lavery; A. Little; K. D. Clements (Marine Biology, 2015)

Accounting for the Impact of Conservation on Human Well‐Being - E.J. MILNER‐GULLAND; J.A. MCGREGOR; M. AGARWALA; G. ATKINSON; P. BEVAN; T. CLEMENTS; T. DAW; K. HOMEWOOD; N. KUMPEL; J. LEWIS; S. MOURATO; B. PALMER FRY; et al. (Conservation Biology, 2014)
Conservationists are increasingly engaging with the concept of human well‐being to improve the design and evaluation of their interventions. Since the convening of the influential Sarkozy Commission in 2009, development researchers have been refining conceptualizations and frameworks to understand and measure human well‐being and are starting to converge on a common understanding of how best to do this. In conservation, the term human well‐being is in widespread use, but there is a need for guidance on operationalizing it to measure the impacts of conservation interventions on people. We present a framework for understanding human well‐being, which could be particularly useful in conservation. The framework includes 3 conditions; meeting needs, pursuing goals, and experiencing a satisfactory quality of life. We outline some of the complexities involved in evaluating the well‐being effects of conservation interventions, with the understanding that well‐being varies between people and over time and with the priorities of the evaluator. Key challenges for research into the well‐being impacts of conservation interventions include the need to build up a collection of case studies so as to draw out generalizable lessons; harness the potential of modern technology to support well‐being research; and contextualize evaluations of conservation impacts on well‐being spatially and temporally within the wider landscape of social change. Pathways through the smog of confusion around the term well‐being exist, and existing frameworks such as the Well‐being in Developing Countries approach can help conservationists negotiate the challenges of operationalizing the concept. Conservationists have the opportunity to benefit from the recent flurry of research in the development field so as to carry out more nuanced and locally relevant evaluations of the effects of their interventions on human well‐being. Consideración del Impacto de la Conservación sobre el Bienestar Humano

A bioenergetic framework for the temperature dependence of trophic interactions - Benjamin Gilbert; Tyler D. Tunney; Kevin S. McCann; John P. DeLong; David A. Vasseur; Van Savage; Jonathan B. Shurin; Anthony I. Dell; Brandon T. Barton; Christopher D.G. Harley; Heather M. Kharouba; Pavel Kratina; et al. (Ecology Letters, 2014)
Changing temperature can substantially shift ecological communities by altering the strength and stability of trophic interactions. Because many ecological rates are constrained by temperature, new approaches are required to understand how simultaneous changes in multiple rates alter the relative performance of species and their trophic interactions. We develop an energetic approach to identify the relationship between biomass fluxes and standing biomass across trophic levels. Our approach links ecological rates and trophic dynamics to measure temperature‐dependent changes to the strength of trophic interactions and determine how these changes alter food web stability. It accomplishes this by using biomass as a common energetic currency and isolating three temperature‐dependent processes that are common to all consumer–resource interactions: biomass accumulation of the resource, resource consumption and consumer mortality. Using this framework, we clarify when and how temperature alters consumer to resource biomass ratios, equilibrium resilience, consumer variability, extinction risk and transient vs. equilibrium dynamics. Finally, we characterise key asymmetries in species responses to temperature that produce these distinct dynamic behaviours and identify when they are likely to emerge. Overall, our framework provides a mechanistic and more unified understanding of the temperature dependence of trophic dynamics in terms of ecological rates, biomass ratios and stability.

A White Paper—Consensus and Recommendations of a Global Harmonization Team on Assessing the Impact of Immunogenicity on Pharmacokinetic Measurements - J. M. Sailstad; L. Amaravadi; A. Clements-Egan; B. Gorovits; H. A. Myler; R. C. Pillutla; S. Pursuhothama; M. Putman; M. K. Rose; K. Sonehara; L. Tang; J. T. Wustner (The AAPS Journal, 2014)

Effect of climate change on corrosion rates of structures in Australia - Nayruti Siddharth Trivedi; Murali Sankar Venkatraman; Clement Chu; Ivan S. Cole (Climatic Change, 2014)

A humanized tissue-engineered in vivo model to dissect interactions between human prostate cancer cells and human bone - Parisa Hesami; Boris M. Holzapfel; Anna Taubenberger; Martine Roudier; Ladan Fazli; Shirly Sieh; Laure Thibaudeau; Laura S. Gregory; Dietmar W. Hutmacher; Judith A. Clements (Clinical & Experimental Metastasis, 2014)

PITX2 and non-canonical Wnt pathway interaction in metastatic prostate cancer - I. Vela; C. Morrissey; X. Zhang; S. Chen; E. Corey; G. M. Strutton; C. C. Nelson; D. L. Nicol; J. A. Clements; E. M. Gardiner (Clinical & Experimental Metastasis, 2014)

Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2014)
HIV-associated neurocognitive disorder (HAND), characterized by a wide spectrum of behavioral, cognitive, and motor dysfunctions, continues to affect approximately 50 % of HIV(+) patients despite the success of combination antiretroviral drug therapy (cART) in the periphery. Of note, potential toxicity of antiretroviral drugs in the central nervous system (CNS) remains remarkably underexplored and may contribute to the persistence of HAND in the cART era. Previous studies have shown antiretrovirals (ARVs) to be neurotoxic in the peripheral nervous system in vivo and in peripheral neurons in vitro. Alterations in lipid and protein metabolism, mitochondrial damage, and oxidative stress all play a role in peripheral ARV neurotoxicity. We hypothesized that ARVs also induce cellular stresses in the CNS, ultimately leading to neuronal damage and contributing to the changing clinical and pathological picture seen in HIV-positive patients in the cART era. In this report, we show that ARVs are neurotoxic in the CNS in both pigtail macaques and rats in vivo. Furthermore, in vitro, ARVs lead to accumulation of reactive oxygen species (ROS), and ultimately induction of neuronal damage and death. Whereas ARVs alone caused some activation of the endogenous antioxidant response in vitro, augmentation of this response by a fumaric acid ester, monomethyl fumarate (MMF), blocked ARV-induced ROS generation, and neuronal damage/death. These findings implicate oxidative stress as a contributor to the underlying mechanisms of ARV-induced neurotoxicity and will provide an access point for adjunctive therapies to complement ARV therapy and reduce neurotoxicity in this patient population.

Elevated prefrontal myo-inositol and choline following breast cancer chemotherapy - Shelli R. Kesler; Christa Watson; Della Koovakkattu; Clement Lee; Ruth O’Hara; Misty L. Mahaffey; Jeffrey S. Wefel (Brain Imaging and Behavior, 2013)

The association of ultraviolet radiation-B (305 nm), season of diagnosis, and latitude on the survival outcome of prostate cancer in the high UV environment of Australia - Visalini Nair-Shalliker; David P. Smith; Sam Egger; Mark S. Clements; Md. Bayzidur Rahman; Bruce K. Armstrong (Cancer Causes & Control, 2013)

Environmental changes impacting Echinococcus transmission: research to support predictive surveillance and control - Jo‐An M. Atkinson; Darren J. Gray; Archie C.A. Clements; Tamsin S. Barnes; Donald P. McManus; Yu R. Yang (Global Change Biology, 2013)
Echinococcosis, resulting from infection with tapeworms Echinococcus granulosus and E. multilocularis, has a global distribution with 2–3 million people affected and 200,000 new cases diagnosed annually. Costs of treatment for humans and economic losses to the livestock industry have been estimated to exceed $2 billion. These figures are likely to be an underestimation given the challenges with its early detection and the lack of mandatory official reporting policies in most countries. Despite this global burden, echinococcosis remains a neglected zoonosis. The importance of environmental factors in influencing the transmission intensity and distribution of Echinococcus spp. is increasingly being recognized. With the advent of climate change and the influence of global population expansion, food insecurity and land‐use changes, questions about the potential impact of changing temperature, rainfall patterns, increasing urbanization, deforestation, grassland degradation and overgrazing on zoonotic disease transmission are being raised. This study is the first to comprehensively review how climate change and anthropogenic environmental factors contribute to the transmission of echinococcosis mediated by changes in animal population dynamics, spatial overlap of competent hosts and the creation of improved conditions for egg survival. We advocate rigorous scientific research to establish the causal link between specific environmental variables and echinococcosis in humans and the incorporation of environmental, animal and human data collection within a sentinel site surveillance network that will complement satellite remote‐sensing information. Identifying the environmental determinants of transmission risk to humans will be vital for the design of more accurate predictive models to guide cost‐effective pre‐emptive public health action against echinococcosis.

Remediation of Uranium-contaminated Groundwater by Sorption onto Hydroxyapatite Derived from Catfish Bones - S. A. Chattanathan; T. P. Clement; S. R. Kanel; M. O. Barnett; N. Chatakondi (Water, Air, & Soil Pollution, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Estimating prevalence of distant metastatic breast cancer: a means of filling a data gap - Mark S. Clements; David M. Roder; Xue Qin Yu; Sam Egger; Dianne L. O’Connell (Cancer Causes & Control, 2012)

Unincorporated iron pool is linked to oxidative stress and iron levels in Caenorhabditis elegans - Natalie A. Rangel; Lawrence Lin; Kanyasiri Rakariyatham; Albert Bach; Kim Trinh; Matthew H. S. Clement; Chandra Srinivasan (BioMetals, 2012)

Components of the neural signal underlying congenital nystagmus - Ozgur E. Akman; David S. Broomhead; Richard V. Abadi; Richard A. Clement (Experimental Brain Research, 2012)

Formative Research on Perceptions of Biobanking: What Community Members Think - John S. Luque; Gwendolyn P. Quinn; Francisco A. Montel-Ishino; Mariana Arevalo; Shalanda A. Bynum; Shalewa Noel-Thomas; Kristen J. Wells; Clement K. Gwede; Cathy D. Meade (Journal of Cancer Education, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Concentrations of bisphenol A in the composite food samples from the 2008 Canadian total diet study in Quebec City and dietary intake estimates - X.-L. Cao; C. Perez-Locas; G. Dufresne; G. Clement; S. Popovic; F. Beraldin; R.W. Dabeka; M. Feeley (Food Additives & Contaminants: Part A, 2011)

Identification of a novel prostate cancer susceptibility variant in the KLK3 gene transcript - Z. Kote-Jarai; A. Amin Al Olama; D. Leongamornlert; M. Tymrakiewicz; E. Saunders; M. Guy; G. G. Giles; G. Severi; M. Southey; J. L. Hopper; K. C. Sit; J. M. Harris; et al. (Human Genetics, 2011)

Characterization of the carbon fluxes of a vegetated drained lake basin chronosequence on the Alaskan Arctic Coastal Plain - D. ZONA; W. C. OECHEL; K. M. PETERSON; R. J. CLEMENTS; K. T. PAW U; S. L. USTIN (Global Change Biology, 2010)
Greenhouse gas fluxes from vegetated drained lake basins have been largely unstudied, although these land features constitute up to 47% of the land cover in the Arctic Coastal Plain in northern Alaska. To describe current and to better predict future sink/source activity of the Arctic tundra, it is important to assess these vegetated drained lake basins with respect to the patterns of and controls on gross primary production (GPP), net ecosystem exchange, and ecosystem respiration (ER). We measured CO 2 fluxes and key environmental variables during the 2007 growing season (June through August) in 12 vegetated drained lake basins representing three age classes (young, drained about 50 years ago; medium, drained between 50 and 300 years ago; and old, drained between 300 and 2000 years ago, as determined by Hinkel et al. , 2003) in the Arctic Coastal Plain. Young vegetated drained lake basins had both the highest average GPP over the summer (11.4 gCO 2 m −2 day −1 ) and the highest average summer ER (7.3 gCO 2 m −2 day −1 ), while medium and old vegetated drained lake basins showed lower and similar GPP (7.9 and 7.2 gCO 2 m −2 day −1 , respectively), and ER (5.2 and 4 gCO 2 m −2 day −1 , respectively). Productivity decreases with age as nutrients are locked up in living plant material and dead organic matter. However, we showed that old vegetated drained lakes basins maintained relatively high productivity because of the increased development of ice‐wedge polygons, the formation of ponds, and the re‐establishment of very productive species. Comparison of the seasonal CO 2 fluxes and concomitant environmental factors over this chronosequence provides the basis for better understanding the patterns and controls on CO 2 flux across the coastal plain of the North Slope of Alaska and for more accurately estimating current and future contribution of the Arctic to the global carbon budget.

Computer Modeling of Controlled Microsphere Release and Targeting in a Representative Hepatic Artery System - Christopher A. Basciano; Clement Kleinstreuer; Andrew S. Kennedy; William A. Dezarn; Emily Childress (Annals of Biomedical Engineering, 2010)

Foraging Response of Turkish Honey Bee Subspecies to Flower Color Choices and Reward Consistency - Ibrahim Cakmak; Daniel S. Song; T. Andrew Mixson; Eduardo Serrano; Meredith L. Clement; Amy Savitski; Ge’Andra Johnson; Tugrul Giray; Charles I. Abramson; John F. Barthell; Harrington Wells (Journal of Insect Behavior, 2010)

Analysis of information used in the management of plant genetic resources: a case study from northwestern Mato Grosso, Brazil - Jorge L. Vivan; Peter H. May; Luís H. H. da Cunha; Walter S. de Boef; Charles R. Clement (Agroforestry Systems, 2009)

Airflow and Nanoparticle Deposition in a 16-Generation Tracheobronchial Airway Model - Zhe Zhang; Clement Kleinstreuer; Chong S. Kim (Annals of Biomedical Engineering, 2008)

Mechanical ventilation and volutrauma: pros and cons of high lung volumes - C. Pastore; F. Pirrone; S. Mazzola; M. G. Clement; M. Albertini (Veterinary Research Communications, 2008)

Development of SHRIMP - T. R. Ireland*; S. Clement; W. Compston; J. J. Foster; P. Holden; B. Jenkins; P. Lanc; N. Schram; I. S. Williams (Australian Journal of Earth Sciences, 2008)

Effects of environmental stress on intertidal mussels and their sea star predators - Laura E. Petes; Morgan E. Mouchka; Ruth H. Milston-Clements; Tracey S. Momoda; Bruce A. Menge (Oecologia, 2008)

High levels of genetic divergence and inbreeding in populations of cupuassu (Theobroma grandiflorum) - Rafael M. Alves; Alexandre M. Sebbenn; Angela S. Artero; Charles Clement; Antonio Figueira (Tree Genetics & Genomes, 2007)

Intravenous Infusion of Nitric Oxide in Experimental Pulmonary Hypertension: Biotransformation and Haemodynamics - F. Pirrone; M. Albertini; S. Mazzola; C. Pastore; M. G. Clement; M. C. Benfatto; G. Aldini; M. Carini (Veterinary Research Communications, 2007)

Carbon Monoxide Induced Prevention of Vascular Ristenosis is not Related to Nitric Oxide Activity - S. Mazzola; M. Albertini; C. Pastore; F. Pirrone; M. G. Clement (Veterinary Research Communications, 2007)

Identification of the endangered Australian orchid Microtis angusii using an allele-specific PCR assay - Nicola S. Flanagan; Rod Peakall; Mark A. Clements; J. Tupac Otero (Conservation Genetics, 2007)

Conservation of taxonomically difficult species: the case of the Australian orchid, Microtis angusii - Nicola S. Flanagan; Rod Peakall; Mark A. Clements; J. Tupac Otero (Conservation Genetics, 2006)

Nonlinear time series analysis of jerk congenital nystagmus - O. E. Akman; D. S. Broomhead; R. A. Clement; R. V. Abadi (Journal of Computational Neuroscience, 2006)

Role of the Endothelium in the Biotransformation of Sodium Nitroprusside (SNP): In vivo and In vitro Study - F. Pirrone; M. Albertini; S. Mazzola; M. G. Clement; G. Aldini; M. Orioli; M. Carini (Veterinary Research Communications, 2006)

Nitrosylhemoglobin as a Potential Bioactive Storage form of Nitric Oxide (NO) - F. Pirrone; M. Albertini; S. Mazzola; G. Aldini; M. Orioli; M. Carini; R. Maffei Facino; M. G. Clement (Veterinary Research Communications, 2005)

Quality analysis applied on eddy covariance measurements at complex forest sites using footprint modelling - C. Rebmann; M. Göckede; T. Foken; M. Aubinet; M. Aurela; P. Berbigier; C. Bernhofer; N. Buchmann; A. Carrara; A. Cescatti; R. Ceulemans; R. Clement; et al. (Theoretical and Applied Climatology, 2005)

Inhaled Carbon Monoxide (CO) Prevents Lung Oedema Induced by Endotoxic Shock - S. Mazzola; M. Forni; M. Albertini; M.L. Bacci; B. Ciminaghi; M. Lavitrano; E. Seren; M.G. Clement (Veterinary Research Communications, 2004)

Prevalence of interspecific hybrids amongst asexual fungal endophytes of grasses - C. D. Moon; K. D. Craven; A. Leuchtmann; S. L. Clement; C. L. Schardl (Molecular Ecology, 2004)
Epichloë endophytes are fungal symbionts of grasses that span a continuum including asexual mutualists that are vertically transmitted, obligately sexual pathogens that are horizontally transmitted, and mixed‐strategy symbionts with both mutualistic and pathogenic capabilities. Here we show that processes of genome evolution differ markedly for the different symbiont types. Genetic and phylogenetic analysis was conducted of a broad taxonomic, ecological and geographical sample of sexual and asexual isolates, in which were identified and sequenced alleles of genes for β‐tubulin ( tub2 ) and translation elongation factor 1‐α ( tef1 ), and microsatellite alleles were identified by length polymorphisms. The majority of asexual isolates had two or three alleles of most loci, but every sexual isolate had only single alleles for each locus. Phylogenetic analysis of tub2 and tef1 indicated that in all instances of multiple alleles in an isolate, the alleles were derived from different sexual species. It is concluded that, whereas horizontally transmissible species had haploid genomes and speciation occurred cladistically, most of the strictly seedborne mutualists were interspecific hybrids with heteroploid (aneuploid or polyploid) genomes. Furthermore, the phylogenetic evidence indicated that, in at least some instances, hybridization followed rather than caused evolution of the strictly seedborne habit. Therefore, the abundance of hybrid species among grass endophytes, and their prevalence in many host populations suggests a selective advantage of hybridization for the mutualistic endophytes.

Innate immune responses and control of acute simian immunodeficiency virus replication in the central nervous system - Sheila A Barber; David S Herbst; Brandon T Bullock; Lucio Gama; Janice E Clements (Journal of NeuroVirology, 2004)

Lateral injection of oxygen with the Bosporus plume—fingers of oxidizing potential in the Black Sea - Sergey K. Konovalov; George III. W. Luther; Gernot E. Friederich; Donald B. Nuzzio; Bradley M. Tebo; James W. Murray; Temel Oguz; Brian Glazer; Robert E. Trouwborst; Brian Clement; Karen J. Murray; Alexander S. Romanov (Limnology and Oceanography, 2003)
Saline and warm Mediterranean water flowing through the Bosporus Strait maintains a permanent pycnocline with vertical separation of oxic (O 2 ), suboxic (absence of O 2 and H 2 S), and anoxic (H 2 S) zones in the Black Sea. The stable suboxic zone implies restricted vertical mixing of the upper oxic and lower anoxic layers and limited vertical flux of oxygen that cannot balance the upward flux of sulfide. We report data that directly confirm massive lateral injections (>200 km from the Bosporus) of oxygen‐enriched waters of the Bosporus plume, created by the mixing of shallow, cold, intermediate‐layer Black Sea water with Mediterranean water. These plume waters are laterally injected into the oxic layer and, more importantly, into the suboxic and anoxic layers over several small vertical scales (“fingers” of ~5 m) at water densities (σ t ) from 15.0 to 16.4. O 2 injection oxidizes Mn(II) to Mn(III,IV), which then oxidizes H 2 S. The onset of H 2 S detection occurs in deeper waters in the southwest (>170 m; σ t ~= 16.4) relative to the west central Black Sea (110 m; σ t ~= 16.2) and coincides with increased MnO 2 and S 8 formation in the southwest.

Endothelin-1 (ET-1) Involvement in Respiratory Dysfunctions during Endotoxic Shock in the Pig - B. Ciminaghi; M. Albertini; C.L. Lafortuna; S. Mazzola; M.G. Clement (Veterinary Research Communications, 2003)

Measuring the Electrical Stapedius Reflex with Stapedius Muscle Electromyogram Recordings - Ryan S. Clement; Paul M. Carter; Daryl R. Kipke (Annals of Biomedical Engineering, 2002)

Repeated endotoxin exposure induces interstitial fibrosis associated with enhanced gelatinase (MMP-2 and MMP-9) activity - M. Corbel; N. Theret; S. Caulet-Maugendre; N. Germain; V. Lagente; B. Clement; E. Boichot (Inflammation Research, 2001)

Productivity overshadows temperature in determining soil and ecosystem respiration across European forests - I. A. Janssens; H. Lankreijer; G. Matteucci; A. S. Kowalski; N. Buchmann; D. Epron; K. Pilegaard; W. Kutsch; B. Longdoz; T. Grünwald; L. Montagnani; S. Dore; et al. (Global Change Biology, 2001)
Summary This paper presents CO 2 flux data from 18 forest ecosystems, studied in the European Union funded EUROFLUX project. Overall, mean annual gross primary productivity (GPP, the total amount of carbon (C) fixed during photosynthesis) of these forests was 1380 ± 330 gC m −2 y −1 (mean ±SD). On average, 80% of GPP was respired by autotrophs and heterotrophs and released back into the atmosphere (total ecosystem respiration, TER = 1100 ± 260 gC m −2 y −1 ). Mean annual soil respiration (SR) was 760 ± 340 gC m −2 y −1 (55% of GPP and 69% of TER). Among the investigated forests, large differences were observed in annual SR and TER that were not correlated with mean annual temperature. However, a significant correlation was observed between annual SR and TER and GPP among the relatively undisturbed forests. On the assumption that (i) root respiration is constrained by the allocation of photosynthates to the roots, which is coupled to productivity, and that (ii) the largest fraction of heterotrophic soil respiration originates from decomposition of young organic matter (leaves, fine roots), whose availability also depends on primary productivity, it is hypothesized that differences in SR among forests are likely to depend more on productivity than on temperature. At sites where soil disturbance has occurred (e.g. ploughing, drainage), soil espiration was a larger component of the ecosystem C budget and deviated from the relationship between annual SR (and TER) and GPP observed among the less‐disturbed forests. At one particular forest, carbon losses from the soil were so large, that in some years the site became a net source of carbon to the atmosphere. Excluding the disturbed sites from the present analysis reduced mean SR to 660 ± 290 gC m −2 y −1 , representing 49% of GPP and 63% of TER in the relatively undisturbed forest ecosystems.

The GABA a agonist muscimol enhances locomotor activity, but does not alter the behavioural effects of CRH in juvenile spring chinook salmon (Oncorhynchus tshawytscha)† - S. Clements; C.B. Schreck (Fish Physiology and Biochemistry, 2001)

Modelling of congenital nystagmus waveforms produced by saccadic system abnormalities - David S. Broomhead; Richard A. Clement; Mark R. Muldoon; Jonathan P. Whittle; Columba Scallan; Richard V. Abadi (Biological Cybernetics, 2000)

Modeling Microbial Transport and Biodegradation in a Dual-porosity System - Y. Sun; J. N. petersen; J. Bear; T. P. Clement; B. S. Hooker (Transport in Porous Media, 1999)

Prolonged intermittent high intensity exercise impairs neuromuscular performance of the knee flexors - T. H. Mercer; N. P. Gleeson; S. Claridge; S. Clement (European Journal of Applied Physiology, 1998)

Dynamical systems analysis: a new method of analysing congenital nystagmus waveforms - R. V. Abadi; D. S. Broomhead; R. A. Clement; J. P. Whittle; R. Worfolk (Experimental Brain Research, 1997)

Pulsing of multiple nutrients as a strategy to achieve large biologically active zones during in situ carbon tetrachloride remediation - Marlee E.L. Franzen; James N. Petersen; T. Prabhakar Clement; Brian S. Hooker; Rodney S. Skeen (Computational Geosciences, 1997)

Efficacy of HLö-7 and pyrimidoxime as antidotes of nerve agent poisoning in mice - John G. Clement; Arnold S. Hansen; Camille A. Boulet (Archives of Toxicology, 1992)

Macroinvertebrate community responses to copper in laboratory and field experimental streams - William H. Clements; Donald S. Cherry; John Cairns (Archives of Environmental Contamination and Toxicology, 1990)

Biology ofTyta luctuosa [Lep.: Noctuidae] and its potential value as a biological control agent for the weedConvolvulus arvensis - S. S. Rosenthal; S. L. Clement; N. Hostettler; T. Mimmocchi (BioControl, 1988)

Neurovirulence of individual plaque stocks of Herpes simplex virus type 2 strain HG 52 - M. Y. Taha; S. Moira Brown; G. B. Clements (Archives of Virology, 1988)

Larviposition response ofBonnetia comta [Dipt.: Tachinidae] to a kairomone ofAgrotis ipsilon [Lep.: Noctuidae] - S. L. Clement; W. L. Rubink; D. A. McCartney (BioControl, 1986)

Genetic manipulation of the restricted facultative methylotroph Hyphomicrobium X by the R-plasmid-mediated introduction of the Escherichia coli pdh genes - L. Dijkhuizen; W. Harder; L. de Boer; A. van Boven; W. Clement; S. Bron; G. Venema (Archives of Microbiology, 1984)